Estrogen-independent molecular actions of mutant estrogen receptor 1 in endometrial cancer - Blanchard, Zannel; Vahrenkamp, Jeffery M.; Berrett, Kristofer C.; Arnesen, Spencer; Gertz, Jason (Genome Research, 2019)
Estrogen receptor 1 (ESR1) mutations have been identified in hormone therapy–resistant breast cancer and primary endometrial cancer. Analyses in breast cancer suggest that mutant ESR1 exhibits estrogen-independent activity. In endometrial cancer, ESR1 mutations are associated with worse outcomes and less obesity, however, experimental investigation of these mutations has not been performed. Using a unique CRISPR/Cas9 strategy, we introduced the D538G mutation, a common endometrial cancer mutation that alters the ligand binding domain of ESR1, while epitope tagging the endogenous locus. We discovered estrogen-independent mutant ESR1 genomic binding that is significantly altered from wild-type ESR1. The D538G mutation impacted expression, including a large set of nonestrogen-regulated genes, and chromatin accessibility, with most affected loci bound by mutant ESR1. Mutant ESR1 is distinct from constitutive ESR1 activity because mutant-specific changes are not recapitulated with prolonged estrogen exposure. Overall, the D538G mutant ESR1 confers estrogen-independent activity while causing additional regulatory changes in endometrial cancer cells that are distinct from breast cancer cells.